Caer [compact disc] - Twin Shadow (Reprise Records, 2018)
The artist's fourth album to date and falling is a theme that surfaces throughout the album. The album serves as a powerful lens through which Lewis explores his own personal sense of falling, as well as what he has observed about a world that feels as if it's declining. On a larger scale, the album feels extraordinarily current, given what's going on culturally and politically right now.